2015
DOI: 10.1183/13993003.00265-2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased respiratory symptoms in COPD patients living in the vicinity of livestock farms

Abstract: Several studies have investigated the effect of livestock farm emissions on the respiratory health of local residents, but results are inconsistent. This study aims to explore associations between the presence of livestock farms and respiratory health in an area of high-density livestock farming in the Netherlands. We focused especially on associations between farm exposures and respiratory symptoms within subgroups of potentially susceptible patients with a pre-existing lung disease.In total, 14 875 adults (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 35 publications
6
95
2
4
Order By: Relevance
“…Goat farms are present to a lesser extent and did not show significant association with atopy (results not shown). Results of this study confirms the results of two previous studies among non-farming populations which found inverse associations between indicators of livestock farm proximity and allergic rhinitis based on self-reported data25 and EMR 26. As expected, we found that a farm childhood history was associated with a lower prevalence of atopy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Goat farms are present to a lesser extent and did not show significant association with atopy (results not shown). Results of this study confirms the results of two previous studies among non-farming populations which found inverse associations between indicators of livestock farm proximity and allergic rhinitis based on self-reported data25 and EMR 26. As expected, we found that a farm childhood history was associated with a lower prevalence of atopy.…”
Section: Discussionsupporting
confidence: 91%
“…The study population originates from participants of a questionnaire survey (n=14 163) conducted in November – December 2012 which is previously described by Borlée et al 25. Questionnaire respondents who gave consent for further contact for a follow-up study, and who were not working or living on a farm were eligible for a medical survey (n=8714).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology is described in detail by Borlee et al [19]. Participants were selected in a two-step procedure.…”
Section: Study Populationmentioning
confidence: 99%
“…41 One study found a lower prevalence of chronic obstructive pulmonary disease among adults living near farms, although adults already diagnosed with COPD were more likely to experience exacerbations. 42 Conflicting results may occur because of differences in livestock operation size, livestock production practices, microbial exposures, or susceptibility of nearby populations.…”
Section: Discussionmentioning
confidence: 97%